XXIII Open seminar on acoustics Jaszowiec, 6-11 September 1976 - Editorial Committee (Archives of Acoustics)
The Open Seminars on Acoustics have been organized in Poland since 1954 by the Polish Acoustical Society in cooperation with the Committee on Acoustics of the Polish Academy of Sciences. Each Seminar constitutes a review of the up-to-date results of in-vestigations in all branches of acoustics followed in Poland. In recent years the number of participants has been approximately 300 including 10 to 20 participants from abroad. The proceedings of the Seminar are available during the conference and consist of the Polish text with the titles and abstracts in both Polish and English. The XXIII Open Seminar in Jaszowiec will consist mainly of the contributed papers although a few invited papers will also be presented. The official language is Polish with simultaneous translation into English. Address of the Organizing Committee: Chairman of Seminar, Dr A. Opilski, Poli-technika glqska, Gliwice, Polska.